Additive Manufacturing of Fixture for Automated 3D Scanning – Case Study. (2016) - Krznar, Nino; Pilipović, Ana; Šercer, Mladen
Abstract: Additive technologies have their place in process of making new parts, from idea to final product. First step in all additive manufacturing is the development of a 3D CAD model which can be made by 3D modeling in any CAD software or 3D scanning and reverse engineering. When scanning parts in automated measuring cell on rotation table, some kind of fixture or jig is needed to keep part in place. Thin-wall plastic parts tend to deform under effect of their own weight or if they are pressed to tight in fixture. This paper shows case study of developing of 3D CAD model of fixture that holds parts during automated 3D scanning for large number of same parts. Also this special fixture that holds part with its geometry in place is made with additive technology, which enables production of complex geometry with lower costs of production because you need for each product special fixture, which in most cases is impossible or difficult to produce using conventional methods.